Incidence, Clinical Evaluation and Antibiogram of Bacterial Isolates Obtained from Burn Patients - Ali Abuzar Raza, Muhammad Ibrahim, Romah Ishfaq, Iqra Saleem, Muhammad Awais Altaf, Umema Asmat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Microbiological contamination plays salient role in governing the outcome and time span in the hospital for burn victims in burn unit. Therefore, regular supervision of microbes and its resistance pattern is mandatory. The emergence of Multi Drug Resistant (MDR) bacteria provoked researchers to develop new plans to combat against the threat. Objective: To assess the infectious organisms, to know the drug resistance of isolates and ascertain the effectiveness of antibiotics against microbes that are found in burn patients. Methodology: Descriptive case series study performed and Quantitative data was collected in Jan 2019 to April 2019. Two hundred sample from burn patients admitted in Pak Italian Burn Unit Multan was collected, processed for culture, bacterial identifications and to test the antibiotics sensitivity in accordance with CLSI (clinical and laboratory standards institute) guidelines. Results: Gram negative bacteria were 189 (94.5%) and gram positive were 11 (5.5%).Organisms isolated were Proteus vulgaris 53 (26.5%) followed by Escherichia coli 47 (23.5%), Pseudomonas aeruginosa 45 (22.5%), Enterobacter 44 (22%) and Staphylococcus aureus 11 (5.5%). Imipenem 156 (78%), Meropenem150 (75%), Moxifloxacin 17(8.5%), Levofloxacin 67 (33.5%), Piperacillin/Tazobactam 123 (61.5%), Oxifloxacin 22 (11%) and Amikacin 16 (8%) were used for antibiotic sensitivity. Practical implication: Our study results can helpful for all health care personals to select new regime of antibiotics which significantly declined in all types of burn patients and also we are able to decrease the mortality rate in such patients. Assertive contagion limitations can helpful in confining the disease and proliferation of MDR pathogens. Conclusion: This study proved to be successful because antibiotic associated complications were decreased significantly as a result mortality rate declination was also noticed in all the types of burn patients. Keywords: Antibiogram, Burn, Clinical evaluations, Infection, Multi drug resistance (MDR), Mortality.